Influence of feeding regimen on growth and steer finishing - Müller, Lauro; Primo, Armando Teixeira (Pesquisa Agropecuaria Brasileira, 2014)
Forty Hereford steers were used to study the effect of ryegrass (Lolium multiflorum Lam.) supplementation during the winter at weaning time (first winter) and/or from 18 to 24 months of age (second winter) on their growth, in comparison with steers that were kept always in native pasture. The animals that grazed ryegrass during the first and second winter reached the live weight of 430 kg at two years of age and were slaughtered. Those that had access to the ryegrass only in the first or only in the second winter, obtained the same weight at approximately three years; and those that were kept exclusively in native grasses, reached it at four years of age. Carcass evaluation proved that the steers that had better nutrition in the first winter, produced carcasses with better muscling and adequate finish. The four-year old steers presented carcasses with poor proportion of muscle and a quite high percentage of bone. The need of a good feeding regime to reduce the slaughtering age and to better the carcass quality was evidenced.